Substitusi Lupin (Lupineus luteus) terhadap Kedelai (Glycine max) dalam Pembuatan Kembang Tahu - S. Widowati; Dayani Dayani; B.A.S. Santosa (agriTECH, 1999)
Soy-lupines film (yuba) were prepared from three combinations of soybean and lupines = 75 : 25 ; 50 : 50; and 25 : 75. Traditional method was used to process soy-lupines film with variation of pH (8 and 10) and water addition (10 and 12 times of raw material weight). The products were characterized for their chemical composition, yield and organoleptics properties. Result showed that to produce the acceptable protein film that gave an average of 35% yield, lupines could subtitute soybean up to 50%.